Application of Epoxy Resin for Improvement of the Banana Stem- Acoustic Panel - Riduan, Mohd A.; Jalil, Mohd Jumain; Azmi, Intan Suhada; Habulat, Afifudin; Raofuddin, Danial N. A.; Habri, Hamzah Hafizuddin; Azmi, Mohamad Heiry Mohd (Recent Innovations in Chemical Engineering, 2022)
Background: Greener epoxidation by using vegetable oil to create an ecofriendly epoxide is being studied because it is a more cost-effective and environmentally friendly commodity that is safer than non-renewable materials. The aim of this research is to come up with low-cost solutions for banana trunk acoustic panels with kinetic modelling of epoxy-based palm oil. Methods: In this study, the epoxidation of palm oleic acid was carried out by in situ performic acid to produce epoxidized palm oleic acid. Results: Banana trunk acoustic panel was successfully innovated based on the performance when the epoxy was applied. Lastly, a mathematical model was developed by using the numerical integration of the 4th order Runge-Kutta method, and the results showed that there is a good agreement between the simulation and experimental data, which validates the kinetic model. Conclusion: Overall, the peracid mechanism was effective in producing a high yield of epoxy from palm oleic acid that is useful for the improvement of acoustic panels based on the banana trunk.
Keywords: kinetic modelling